Inflammatory and non-inflammatory roles for Toll-like receptors in gastrointestinal cancer - West, Alison C; Jenkins, Brendan J (Current pharmaceutical design, 2015)
Collectively, cancers of the gastrointestinal (GI) tract (including the esophagus, stomach, duodenum, colon, rectum, liver, gall bladder and bile ducts) are the most prevalent and deadly worldwide. A common denominator in the pathogenesis of these GI tract cancers is chronic inflammation, as evidenced by the fact that sufferers of inflammatory bowel disease (IBD) are significantly more susceptible to colon cancer than healthy individuals. However, since only a relatively small proportion of individuals with chronic inflammatory conditions such as IBD go on to develop cancer, research has focused on identifying discrepancies in the host immune system that may be responsible for promoting carcinogenesis in inflamed tissue. To this end, molecular pathways linking inflammation and cancer are emerging, with one series of candidates being members of the Toll-like receptor family.